When and Why Ancient Art Became Anonymous - Corso, Antonio (Actual Problems of Theory and History of Art, 2021)
In this article, the problem of why ancient art became anonymous in late antiquity is discussed. There are aesthetic reasons: the visual arts are no longer thought to respond to the mimesis but to the ‘phantasia’, thus the images have a transcendent origin and are no longer attributed to specific artists. Moreover, the passage of the Roman Empire from a constitutional monarchy to an absolutistic one implies that monuments are now attributed especially to the imperial patronage, artists and architects are devaluated. The decline of classical culture, the widespread pessimistic feelings, and finally the disengagement of the western part of the Roman Empire from the classical Greek heritage complete this picture. However, ancient artists will become again renowned from the 9th and 10th century onwards.The artists are mentioned and regarded important until Severan times. From this period onwards, the mentioning of artists becomes rare and disappears. This process is due to a radical change in the aesthetic theory (the phantasia becomes more important that the mimesis), to the transformation of the Roman Empire into an absolutistic monarchy, to the decline in classical education, finally to the establishment of a culture which sees works of art as the epiphanies of deities rather than the creations of artists.
Keywords: phantasia; Mimesis; artist; absolutistic monarchy; Severans; anonymity; pessimism; cultural decline